2001
DOI: 10.1002/ssu.1049
|View full text |Cite
|
Sign up to set email alerts
|

Detection of occult metastasis in patients with breast cancer

Abstract: The most important factor affecting the outcome of patients with invasive cancer is whether the tumor has spread, either regionally (to regional lymph nodes) or systemically. However, a proportion of patients with no evidence of systemic dissemination will develop recurrent disease after primary "curative" therapy. Clearly, these patients had occult systemic spread of disease that was undetectable by routinely employed methods (careful pathological, clinical, biochemical, and radiological evaluation). In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…5 When cancer cells enter the lymphatic system, they travel to the lymph nodes (LN) 4 -in the case of breast cancer, to the sentinel nodes in the axilla and intercostal spaces-before entering the bloodstream and subsequent progression to other organs. 4 Axillary LN metastases Although most patients with newly diagnosed breast cancer have operable disease and are therefore considered potentially curable, 6 the probability of all patients who possess histologically confirmed negative LN remaining disease free after five years was calculated to be 85%. 7 Thus, 15% of ''node negative'' patients will probably develop metastatic disease.…”
Section: Breast Cancer Metastasesmentioning
confidence: 99%
See 1 more Smart Citation
“…5 When cancer cells enter the lymphatic system, they travel to the lymph nodes (LN) 4 -in the case of breast cancer, to the sentinel nodes in the axilla and intercostal spaces-before entering the bloodstream and subsequent progression to other organs. 4 Axillary LN metastases Although most patients with newly diagnosed breast cancer have operable disease and are therefore considered potentially curable, 6 the probability of all patients who possess histologically confirmed negative LN remaining disease free after five years was calculated to be 85%. 7 Thus, 15% of ''node negative'' patients will probably develop metastatic disease.…”
Section: Breast Cancer Metastasesmentioning
confidence: 99%
“…6 Consequently, further IHC analysis of the identified epithelial cells using specific breast cancer marker antibodies is required to confirm that these epithelial cells are breast cancer cells. 32 33 This will invariably result in an increase in the time taken and costs incurred in performing such an assay.…”
Section: Flow Cytometrymentioning
confidence: 99%
“…A number of studies have re-evaluated the lymph nodes of breast cancer patients that were considered negative by initial routine histological assessment using hematoxylin and eosin (H&E) staining [5][6][7][8][9][10][11][12][13][14]. They found that 9-32% of previously node-negative cases had occult tumor cell deposits after review, using various methods such as serial sectioning and/or immunohistochemical (IHC) staining [5].…”
Section: Introductionmentioning
confidence: 98%
“…Classically, it is considered that the risk of spread of disease is estimated by factors, such as tumor size, cytonuclear grade, estrogen and progesterone receptors, ploidy, overexpression of CerbB2 (Her2/neu), and the number of positive axillary lymph nodes [3], although the presence of tumor cells in regional lymph nodes is the most important prognostic factor [11][12][13][14]. In recent years, the concept of sentinel lymph node biopsy emerged in breast cancer.…”
Section: Lymph Nodesmentioning
confidence: 99%